Safety and efficacy of remifentanil in patients undergoing bariatric and metabolic surgeries – A systematic review - Abhijit S. Nair; Indira Gurajala; Nitinkumar Borkar; Ujjwalraj Dudhedia; Manamohan Rangaiah; Sandeep Diwan (Indian Journal of Anaesthesia)
Background and Aims: Obese patients undergoing bariatric and metabolic surgeries have a high chance of respiratory depression and could need admission to an intensive care unit or a high-dependency unit. Several studies have compared remifentanil to other opioids or non-opioids in these patients. This review investigated the efficacy and safety of remifentanil in bariatric and metabolic surgeries. Methods: After registering with PROSPERO, we searched PubMed/Medline, Ovid, CINAHL and the Cochrane Library with relevant keywords to find studies in which remifentanil was compared to other opioids or non-opioids in adult patients undergoing bariatric and metabolic surgeries. We used the risk of bias-2 tool to assess bias and Grading of Recommendation, Assessment, Development and Evaluation to determine the level of evidence. RevMan 5.4 was used to perform a quantitative meta-analysis. Results: Of the 121 articles retrieved from the database search, seven articles fulfilled the inclusion criteria. The overall bias was low in five studies and high in two studies. There was significant heterogeneity in the control group, which comprised opioids and also non-opioids like labetalol, dexmedetomidine and lignocaine. A quantitative meta-analysis was not reported due to a lack of comparable data for a meaningful quantitative meta-analysis. Conclusion: The results of this systematic review neither support nor refute the use of remifentanil in patients undergoing bariatric and metabolic surgeries, compared to other medications. Further studies are needed to investigate its efficacy and safety in these patients.